A High-Quality Grapevine Downy Mildew Genome Assembly Reveals Rapidly Evolving and Lineage-Specific Putative Host Adaptation Genes. (7th March 2019) - Dussert, Yann; Mazet, Isabelle D; Couture, Carole; Gouzy, Jérôme; Piron, Marie-Christine; Kuchly, Claire; Bouchez, Olivier; Rispe, Claude; Mestre, Pere; Delmotte, François
Abstract: Downy mildews are obligate biotrophic oomycete pathogens that cause devastating plant diseases on economically important crops. Plasmopara viticola is the causal agent of grapevine downy mildew, a major disease in vineyards worldwide. We sequenced the genome of Pl. viticola with PacBio long reads and obtained a new 92.94 Mb assembly with high contiguity (359 scaffolds for a N50 of 706.5 kb) due to a better resolution of repeat regions. This assembly presented a high level of gene completeness, recovering 1, 592 genes encoding secreted proteins involved in plant–pathogen interactions. Plasmopara viticola had a two-speed genome architecture, with secreted protein-encoding genes preferentially located in gene-sparse, repeat-rich regions and evolving rapidly, as indicated by pairwise d N /d S values. We also used short reads to assemble the genome of Plasmopara muralis, a closely related species infecting grape ivy ( Parthenocissus tricuspidata ). The lineage-specific proteins identified by comparative genomics analysis included a large proportion of RxLR cytoplasmic effectors and, more generally, genes with high d N /d S values. We identified 270 candidate genes under positive selection, including several genes encoding transporters and components of the RNA machinery potentially involved in host specialization. Finally, the Pl. viticola genome assembly generated here will allow the development of robust population genomics approaches for investigating the mechanisms involved in adaptation to biotic and abiotic selective pressures in this species.